Literasi Digital Umkm Sebagai Strategi Bertahan Dalam Industri Fashion Clothing Di Kota Bandung - Moch Rais Maulana; Ade Yunita Mafruhat (UPT Publikasi Ilmiah (Universitas Islam Bandung), 2024)
Digital literacy is basically the practice of communication, building relationships, thinking, and other activities related to digital media. Digital literacy is not only the technical ability to operate computers as digital equipment, but also the ability to adapt to activities mediated by digital technology, including in the fashion clothing industry. Based on the identification of problems, this research aims to explain the influence of the internet on the development of MSMEs and determine the weaknesses and strengths in the defense of MSMEs against the internet in Bandung City. The research method that will be used in this research is to use a descriptive analysis method with a quantitative approach. In this study the authors used the SWOT analysis analysis method which is used to analyze the strengths and weaknesses of an organization and recognize potential opportunities and threats. Based on the identification of internal and external factors, the strategy that can be carried out in developing the fashion clothing industry in Bandung City is the W-O (weakness-Opportunity) strategy, which is a strategy that utilizes opportunities, namely increasing learning about the digital world and making new innovations to the products produced so that they become differentiators from one clothing to another.